“Happy Copulation”: Blake, visual enthusiasm and gallery culture - Matthews, Susan (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis essay explores the complex issue of Romantic visual enthusiasm –the power to self-generate images – which was seen as both a danger and a necessity to the project of constructing a visual culture for the nation at the end of the eighteenth century. I look at a range of important texts on this issue, beginning with an analysis of the contradictory responses which emerge in John Ireland’s 1798 discussion of Hogarth’s 1760 Enthusiasm Delineated. Ireland’s discussion is significant as it reflects the concerns of his publisher John Boydell, whose Shakespeare Gallery was beginning to falter by the end of the 1790s. The positions adopted by Henry Fuseli (a key artist in Boydell’s project), George Cumberland (a harsh critic of Boydell) and William Blake (passed over by Boydell) provide a map of the debate over visual enthusiasm. Hogarth’s satire represents the enthusiastic audience as inappropriately sexualised and includes an image of monstrous fertility in the figure of Mary Toft. Blake’s phrase ‘happy copulation’ from Visions of the Daughters of Albion reproduces the association of looking, sexuality, and the female gaze found in the satire. But Blake’s positive image of enthusiastic looking is mirrored by the negative account of the power of transformative viewing in the repeated formula ‘He became what he beheld’. In Europe, Blake produces a version of Fuseli’s Titania and Bottom as a critique of the power of the literary gallery to limit the scope of the political imagination. Blake’s powerful response to the experience of the London galleries and his complicated account of the construction of the viewer within the gallery space is suggested in his poetry of the 1790s in which enthusiastic viewing is both celebrated and feared.